COPING MECHANISM CONCERNED WITH CULTURE DIFFERENCES OF OUTER REGION STUDENTS IN THE FIRST YEAR - Maria Wisnu Kanita; Nur Setiawati Dewi (Jurusan Keperawatan, Universitas Diponegoro, 2012)
First year student is one of population who susceptible become stress which one of the causes was because of culture differences between home town and the new region where they took education. Coping mechanism was used by students to cope the culture differences. The first year students’ experiences of coping mechanism became the research base so that experiences description of coping mechanism concerned with culture differences in the first year students were providable. This research was a qualitative study with phenomenological approach using in-depth interview method. The research had been done at PSIK FK UNDIP which involved five outer region students in the first year who never stayed in Java. This research showed that there are differences between respondents’ home town and Java, such as: cultures, infrastructures, environment, and community, which made problems and various feelings. In solving the problems, they used positive and negative coping mechanism. Based on their experience, internal and external aspects were being the self preparation. Culture differences which have never known by students caused problems and various feelings and afterwards turned up the coping mechanism to solve it. Quality of nurse role as a counselor, care giver and rehabilitator can increase the optimum self function of the outer region students in the first year.